Code-Switching in English as a Second Language (ESL) Classroom Settings: A Strategy or a Problem? - Anisah, Nur; Nasrullah, Nasrullah (Asatiza: Jurnal Pendidikan, 2023)
Code-switching, or switching from one language to another, is common in many bilingual and multilingual classrooms. Nonetheless, there have been opposing perspectives on its application in the classroom. While some studies argue that the presence of code-switching is beneficial to teaching language, others regard it as a hindrance to achieving the learning goal of acquiring the target language. This study addresses a research gap concerning teachers' and students' perspectives on code-switching in ESL classrooms, whether it is a strategy or a problem. This research method involves a systematic literature review process that is classified into three stages: planning, implementation, and reporting. Forty-five journal papers were discovered in the initial search string, and 34 were chosen based on inclusion and exclusion criteria for further research. The results of all research contained in journals published from 2012 to 2022 showed that there had been a debate with opposing perspectives over the usage of code-switching in classrooms. The majority of teachers and students perceive the practice of code-switching in ESL classrooms positively. However, many of them are aware of the potential negative consequences. Some individuals are even opposed to code-switching. Furthermore, the data suggested that code-switching might be a useful tool for teachers and students in ESL classrooms, depending on its purposes and functions. This study recommends that teachers use code-switching as needed by considering the purposes and consequences of its use.